Applying an affordances approach and a developmental lens to approach adolescent social media use. (January 2019) - Moreno, Megan A; Uhls, Yalda T
Social media use among adolescents is nearly ubiquitous. Researchers, educators and parents may find the ever-shifting landscape of social media challenging to understand. In this Educational Piece, we describe an affordances approach. Applying an affordances approach to social media can advance our understanding of social media as a set of functions rather than brand name platforms. We present an affordances approach alongside the critical developmental tasks of adolescence. Our goal is to advance our thinking and standards in communicating about social media and adolescents to inform better research and program design.